Understanding workplace violence: a guide for managers and employees - Paludi, Michele Antoinette (Praeger, 2006)
Understanding workplace violence: myths and realities -- What is workplace violence? -- Incidence and impact of workplace violence on employees and organizations -- Contributing factors to workplace violence -- Workplace sexual harassment -- Intimate partner violence as a workplace concern -- Managing violence, aggression, and other abusive behaviors in the workplace